2012
DOI: 10.1016/j.ijid.2012.05.500
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of simple strategies in reducing multidrug resistant bloodstream infections in the NICU of a tertiary care hospital in Karachi, Pakistan

Abstract: Background: Nosocomial infections in the neonatal intensive care unit (NICU) are a cause of increased mortality, length of stay and cost of management. There is limited data on strategies for reducing these infections from developing countries. Therefore we evaluated the effectiveness of implementation of six strategies in reducing the rate of nosocomial bloodstream infections (BSI) due to multidrug resistant organisms (MDRO) in the NICU.Methods: Using a pre and post design, the study was carried out (from Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Few studies address the role of nappies in the aetiology of neonatal infection. Disposable compared with cloth nappies reduce the risk of sepsis,31 and gloves for nappy changes may decrease the risk of spread of infections when used in conjunction with other infection control strategies such as handwashing certification 32. While gloves may also reduce spread of vancomycin-resistant Enterococcus spp onto healthcare worker hands, they are not fool-proof, rendering handwashing after glove removal essential 33…”
Section: Discussionmentioning
confidence: 99%
“…Few studies address the role of nappies in the aetiology of neonatal infection. Disposable compared with cloth nappies reduce the risk of sepsis,31 and gloves for nappy changes may decrease the risk of spread of infections when used in conjunction with other infection control strategies such as handwashing certification 32. While gloves may also reduce spread of vancomycin-resistant Enterococcus spp onto healthcare worker hands, they are not fool-proof, rendering handwashing after glove removal essential 33…”
Section: Discussionmentioning
confidence: 99%
“…The current study also found that training can enhance the self-reported behavioral compliance of medical staff, which was similar to the results of several other studies ( 12 , 21 , 24 ). In addition, one study ( 29 ) whose interventions included hand hygiene training and certification for medical staff effectively reduced MDRO infection. Training can not only improve the medical staff's grasp of infection prevention and control knowledge, deepen their understanding of MDRO infection prevention and control, and make them realize the importance of prevention and control but also regulate the behavior of doctors and nurses, which is an important means of improving the KAP of medical staff toward MDRO infection prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Effective infection control programs are able to considerably reduce rates of HAI in neonates, including those caused by multi-resistant microorganisms. [1][2][3][4] Carbapenem-resistant Gram-negative bacteria (CR-GNB) are considered by the World Health Organization (WHO) to be critical in relation to the need to control the spread and research of new effective antimicrobials. The main measures described for prevention and control of these bacteria include: hand hygiene, contact precaution, patient isolation, environmental cleanliness, crop surveillance and monitoring, auditing and feedback of infection prevention and control interventions.…”
Section: Introductionmentioning
confidence: 99%